Multilevel inverter: harmonic analysis with and without filters for RL load using SPWM techniques - Champa Patanegere Nagarajappa; Abhay Anandarao Deshpande (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Multilevel inverter (MLI) gains more attraction compared to conventional inverter as it generates a staircase output voltage that mimics sine waves of desired output voltage. Cascaded H-bridge (CHB) topology is taken into consideration owing to several benefits over conventional inverters. Various levels of CHB (3 and 5 level) inverters are compared on diverse parameters. In this paper level shift sinusoidal pulse width modulation technique is considered resulting in reduced lower order harmonic (LOH) distortion and improve the quality of output current and voltage depending on the load. Since, the LOH are too dangerous for power electronic circuits. An attempt to shift all the LOH above 50th order depending on the modulation technique with analogy for selecting an appropriate switching frequency is highlighted. The effect of change in switching frequency and modulation index (MI) on RMS output voltage, % voltage total harmonic distortion (VTHD), output power factor with different modulation techniques such as phase disposition pulse width modulation (PsD PWM), phase opposite disposition (POD PWM), alternative phase opposition disposition (APOD PWM) is portrayed in the paper. Further, to boost the performance a unique filter circuits with optimal design values of Inductance and capacitance driven with IEEE 519-2022 standards. The effectiveness in terms of with and without filter is verified and validated using MATLAB.